2017
DOI: 10.1039/c7cy01724c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Co–Mo sulfide catalyst with a hollow structure for highly efficient hydrodesulfurization of dibenzothiophene

Abstract: Co–Mo sulfides with tube-like structures exhibit super high activity for HDS of DBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
3
2
Order By: Relevance
“…As shown in Table S2, the conversion and the total S-free product selectivity reached 100% and >99.9%, respectively. In comparison with the previous investigations, ,, these reaction temperatures were lowered by about 50 °C, presenting its high HDS activity.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…As shown in Table S2, the conversion and the total S-free product selectivity reached 100% and >99.9%, respectively. In comparison with the previous investigations, ,, these reaction temperatures were lowered by about 50 °C, presenting its high HDS activity.…”
Section: Resultscontrasting
confidence: 50%
“…As shown in Table S2, the conversion and the total S-free product selectivity reached 100% and >99.9%, respectively. In comparison with the previous investiga- tions, 32,71,72 these reaction temperatures were lowered by about 50 °C, presenting its high HDS activity. More importantly, we had scaled up the catalyst preparation procedure to 20-fold and 200-fold, producing 16.1 and 169.5 g CoS-MoS 2 for one time, respectively.…”
Section: Deoxygenation Activity Of Cos-mos 2 Catalystscontrasting
confidence: 56%
“…For the Mo 3d regions, the spectra could be deconvoluted into 3 signals: Mo oxide phase MoO 3 ( vi ) with a doublet at 233.3 eV and 236.5 eV, intermediate sulfided state Mo oxysulfide MoO x S y ( v ) with a doublet at 231.7 eV and 234.9 eV, and disulfide MoS 2 ( iv ) with a doublet at 229.3 eV and 232.5 eV. 63,64 The obtained proportions of different Mo species in Co 4 Mo 12 sulfides of 200 °C and 400 °C are presented in Table 1. It can be found that the proportion of MoS 2 ( iv ) on Co 4 Mo 12 sulfide of 200 °C is only 20.46%, indicating a lower degree of sulfidation.…”
Section: Resultsmentioning
confidence: 99%
“…Jaramillo et al combined theory and experiment to demonstrate that Fe 0.5 Co 0.5 P exhibits the highest HER activity of the investigated TMPs . Despite great advances achieved, the present synthetic processes for TMSs and TMPs particularly with complex compositions are relatively complicated and harsh, and always involve organic solvents, hazardous gas (H 2 S), or additional phosphorus/sulfur sources (NaH 2 PO 2 , CH 3 CSNH 2 , CH 4 N 2 S, CS 2 ) . Therefore, the development of an easy and facile route for large‐scale preparing TMSs and TMPs‐based catalysts with desirable OER activity is extremely expected.…”
Section: Methodsmentioning
confidence: 99%